2021
DOI: 10.1002/batt.202100096
|View full text |Cite
|
Sign up to set email alerts
|

An Invitation to Engage with Computational Modeling: User‐Friendly Tool for In Silico Battery Component Generation and Meshing

Abstract: With the growing interest in battery computational modeling to work hand‐in‐hand with experiments, the lack of user‐friendly software, in particular accessible for experimentalists, is an impediment to its development. In the battery field, time dependent 3D‐resolved computational modeling is a more promising approach compared to trial and error to capture the impact of the mesostructure of components (e. g. electrode, separator) on the electrochemical and transport properties of the cell. In this Concept, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…To grasp how the propagation of error could occur during the meshing process, Figure 12 shows generated meshes for different numbers of elements as a function of the time they took to be generated, for an electrode sub‐volume arising from nano‐CT (Figure 12a). INNOV, the meshing algorithm developed by us, was used for the mesh illustration discussed here [32,33] . It can be observed that there is a significant improvement of the mesh when comparing the coarser mesh (light blue) with the finer mesh (red).…”
Section: Why Does the Mesh Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…To grasp how the propagation of error could occur during the meshing process, Figure 12 shows generated meshes for different numbers of elements as a function of the time they took to be generated, for an electrode sub‐volume arising from nano‐CT (Figure 12a). INNOV, the meshing algorithm developed by us, was used for the mesh illustration discussed here [32,33] . It can be observed that there is a significant improvement of the mesh when comparing the coarser mesh (light blue) with the finer mesh (red).…”
Section: Why Does the Mesh Matter?mentioning
confidence: 99%
“…INNOV, the meshing algorithm developed by us, was used for the mesh illustration discussed here. [32,33] It can be observed that there is a significant improvement of the mesh when comparing the coarser mesh (light blue) with the finer mesh (red). Whether it is the interface between the AM and the CBD or the AM morphology both have a smoother aspect in the meshes with the highest amount of elements.…”
Section: Error Propagation Through the Meshmentioning
confidence: 99%
“…[95] A freeware alternative called INNOV is also available, which allows users to generate battery electrodes by controlling for example the shape of carbon-binder domain partially covering the surface of active material particles. [96][97][98]…”
Section: Digitalization Framework and Apismentioning
confidence: 99%
“…Moreover, our INNOV algorithm that can control the morphology of the CBD was used to add the CBD as a film or as an aggregate. 13 For a given NMC skeleton HP-1, arose two electrodes with CBD as film (HP-1film-1, HP-1film-2) and two with CBD as aggregates (HP-1agg-1, HP-1agg-2). The difference between the two configurations can be seen in Figure 1(b,c) for a slice of respectively HP-1film-1 and HP-1agg-1.…”
mentioning
confidence: 99%
“…The difference between the two configurations can be seen in Figure 1(b,c) for a slice of respectively HP-1film-1 and HP-1agg-1. Finally, the electrode mesostructures were meshed using INNOV 13,14 (with all the NMC particles individually identified), and fed to a Newman-based 15,16 3-D model used in our previous studies, 5,17 to simulate a discharge at rate of 3C. In Figure 2a, the discharge curves obtained for the four different cases are represented with the dispersion related to the stochastic nature of the electrode generation.…”
mentioning
confidence: 99%